Research on efficient and scalable private set intersection cardinality schemes - LI Gongli; LIU Weichen; ZHENG Dong (Tongxin xuebao)
To address the issue of high computational overhead in existing two-party private set intersection cardinality (PSI-CA) protocols, an efficient two-party PSI-CA protocol was proposed. Oblivious key-value store (OKVS) and oblivious key-sharing pseudorandom function (OKS-PRF) were leveraged by this protocol to hide information of intersection elements, with execution time being significantly optimized. Moreover, the protocol could be extended to multi-party PSI-CA scenarios. Experimental results show that when the set size is <alternatives>220 <?fx-imagestate width="3.72533321" height="2.45533323"?> <?fx-imagestate width="3.72533321" height="2.45533323"?> </alternatives>, the proposed two-party PSI-CA protocol completes in 36.61 seconds, and the execution speed is 1.8 times than the fastest existing two-party protocol. When the number of participants is <alternatives>23 <?fx-imagestate width="2.70933342" height="2.45533323"?> <?fx-imagestate width="2.70933342" height="2.45533323"?> </alternatives>and the set size is <alternatives>220 <?fx-imagestate width="3.72533321" height="2.45533323"?> <?fx-imagestate width="3.72533321" height="2.45533323"?> </alternatives>, the proposed multi-party PSI-CA protocol completes in 115.32 seconds and can resist collusion among up to <alternatives>N-2 <?fx-imagestate width="7.70466709" height="2.28600001"?> <?fx-imagestate width="7.70466709" height="2.28600001"?> </alternatives> participants.